2022
DOI: 10.1364/boe.473475
|View full text |Cite
|
Sign up to set email alerts
|

Coarse-scale optoretinography (CoORG) with extended field-of-view for normative characterization

Abstract: Optoretinography (ORG) has the potential to be an effective biomarker for light-evoked retinal activity owing to its sensitive, objective, and precise localization of retinal function and dysfunction. Many ORG implementations have used adaptive optics (AO) to localize activity on a cellular scale. However, the use of AO restricts field-of-view (FOV) to the isoplanatic angle, necessitating the montaging of multiple regions-of-interest to cover an extended field. In addition, subjects with lens opacities, increa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Optoretinography has recently emerged as a technique for measuring photoreceptor function in the living human retina 29 35 , 37 , 39 , 47 . In the present study, ORG signals in parafoveal retina were successfully obtained using AOSLO in both normal-sighted participants and those diagnosed with CHM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Optoretinography has recently emerged as a technique for measuring photoreceptor function in the living human retina 29 35 , 37 , 39 , 47 . In the present study, ORG signals in parafoveal retina were successfully obtained using AOSLO in both normal-sighted participants and those diagnosed with CHM.…”
Section: Discussionmentioning
confidence: 99%
“…ORG amplitudes in previous studies likewise have shown similar ranges across individuals, with ORG amplitudes in some cases varying by a factor of two 30 , 31 . The cause of this inter-subject variability is unknown though possible contributing factors include outer segment length, axial length, and dilated pupil size 39 in additional to biological variables such as age and sex. In the present study, the normal-sighted participant with the lowest ORG amplitude was female.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pORGs are determined using the argument (or phase) of the complex OCT signal, and are typically calculated by determining the change in phase as referenced to the cone boundary. This is then related to the change in optical path length ( 29 35 ). Conversely, iORGs are created from changes in the amplitude of backscattered light from photoreceptors using adaptive optics flood illumination ophthalmoscopes ( 26 , 36 ) adaptive optics scanning light ophthalmoscopes (AOSLOs) ( 25 , 37 , 38 ), and OCTs ( 39 43 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although a few studies have extracted phase-sensitive ORG signals from speckle patterns by spatial averaging, this approach could not maintain the spatial heterogeneity (20)(21)(22). It was unclear how the actual nanoscopic tissue movement could be interpreted from the phase component of speckle patterns or how other tissues such as the retinal pigment epithelium (RPE) and the Bruch's membrane (BrM) behave in response to light stimuli, as their signals are mixed in these speckle patterns.…”
Section: Introductionmentioning
confidence: 99%